Risk to plant health of Ditylenchus destructor for the EU territory. (7th December 2016) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The EFSA Panel on Plant Health performed a pest risk assessment on Ditylenchus destructor, the potato rot nematode, for the EU. It focused the assessment of entry, establishment, spread and impact on two crops: potato ( Solanum tuberosum ) and tulip ( Tulipa spp.). The main pathways for entry of D. destructor into the EU and for spread of this nematode within the EU are plants for planting, including seed potatoes and flower bulbs. These commodities are also the main targets for the assessment of the impact. A modelling approach was used to quantitatively estimate entry, spread and impact. Literature and expert judgement were used to estimate model parameters, taking into account uncertainty. A baseline scenario with current pest‐specific phytosanitary regulations was compared with alternative scenarios without those specific regulations or with additional risk reduction options. Further information is provided on the host range of D. destructor and on survival of the nematode in soil in the absence of hosts. The Panel concludes that the entry of D. destructor with planting material from third countries is small compared to the yearly intra‐EU spread of this nematode with planting material. Changes in pest‐specific regulations have little influence on entry of the pest as other non‐specific regulation already lead to a good level of protection against the introduction of the nematode into the pest risk assessment (PRA) area. It is also concluded that the whole PRA area is suitable for establishment of D. destructor, but there is insufficient information to make a statement on the persistence of newly introduced populations in the entire PRA area. Impacts of this nematode on the quantity and quality of potato are considered negligible. The impact on flower bulb production in the EU is considered as very low.